Financial Ratio Analysis at PT Bank Mandiri (Persero) Tbk Over The Period 2018-2022 - Ratmanasuci , Novinda Dian Adityaning; Digdowiseiso , Kumba (CV ODIS, 2024)
The aim of this research is to determine the liquidity ratio, solvency ratio and profitability at PT Bank Mandiri (Persero) Tbk for the 2018–2022 period and financial ratios at PT Bank Mandiri (Persero) Tbk based on analysis of the liquidity, solvency and profitability ratios for the 2018–2022 period. The method of this research is a quantitative descriptive method. The result of this discussion is an analysis of the financial ratios at PT Bank Mandiri (Persero) Tbk for 2018–2022, summarized as follows: From Bank Mandiri's liquidity ratios for the 2018–2022 period, it can be concluded that Bank Mandiri's liquidity is generally categorized as good. The decline in liquidity in 2020–2022 is normal due to the Covid-19 pandemic. The solvency ratio has also decreased due to Indonesia's economic conditions during the Covid-19 pandemic, but is still categorized as good. Bank Mandiri's profitability ratio experienced a decline during the Covid-19 pandemic in 2020, but increased again and even in 2022 it was able to achieve the best profitability ratio figure in the 5 year period